Comparison of effectiveness of different training tools on the level of knowledge about emergency management of avulsed teeth in non-dentists - Zekiye Şeyma Gümüşboğa; Gülsüm Duruk (Digital Health, 2023)
Objective Tooth avulsion is a type of trauma requiring an emergency response, and the level of knowledge of non-dentists on the emergency management of avulsed teeth is important for the prognosis of affected teeth. This study aimed to compare the effectiveness of training given using different tools on the level of knowledge about the emergency management of avulsed teeth in non-dentists. Methods A total of 125 individuals (female, 32.8%; male, 67.2%; mean age, 38.5 ± 7.32 years) participated in the study. The participants were randomly assigned to three groups, and the training was offered to these groups using different training tools (group 1, storybook; group 2, poster; group 3, ToothSOS App). A survey was conducted on all participants to measure their knowledge levels before training (T 0 ), immediately after (T 1 ), and 1 month later (T 2 ). The Mann–Whitney U, Kruskal–Wallis, Wilcoxon, and Friedman tests were used for statistical analysis. Results The participants’ mean correct answer scores on a scale from 0 to 21 were 7.76 ± 4.00, 5.47 ± 4.71, and 7.38 ± 2.96 at T0 in groups 1, 2, and 3, respectively, and their mean scores increased to 14.68 ± 4.10, 13.74 ± 3.28, and 13.86 ± 3.01 at T 1 and 13.41 ± 3.34, 12.34 ± 3.77, and 13.66 ± 3.56 at T 2 . The correct answer scores increased significantly at both T 1 and T 2 in all groups ( p  < 0.001). Conclusion None of the training tools used in the study was superior in increasing the level of knowledge. More comprehensive and long-term studies on this subject are needed.